Skeletal muscle index, grip strength, and physical performance as predictors of severe chemotherapy toxicity among older adults with malignancy - Efthymios Papadopoulos; Dmitry Rozenberg; Andy Kin On Wong; Sharon Hiu Ching Law; Sarah Costa; Angela M. Cheung; Shabbir M. H. Alibhai (PLoS ONE, 2025)
Background Skeletal muscle index (SMI), grip strength, and physical performance have been shown to predict clinically relevant outcomes in geriatric oncology. However, their predictive ability for chemotherapy toxicity is poorly understood. We examined whether SMI, grip strength, or physical performance are independently associated with severe toxicity among older adults receiving chemotherapy. Methods Older adults (≥65y) who had received chemotherapy at an academic cancer center between June 2015 and June 2022 were included in the analysis. SMI prior to chemotherapy was determined via computed tomography (CT), using the entire cross-sectional area of the muscle (cm 2 ) at the third lumbar vertebra (L3) divided by the square of patient height in meters. Grip strength and lower extremity physical performance were measured prior to chemotherapy. Multivariable logistic regression was used to examine the independent associations between SMI, low grip strength, and low physical performance with severe (grade≥3) chemotherapy toxicity. Results Of the 115 older adults in the study, 71.3% were males. The most common disease site was genitourinary (53.9%) and most participants received chemotherapy with palliative intent (67.8%). A total of 69 (60.0%) participants experienced at least one grade ≥3 toxicity during the study. In multivariable analyses, low grip strength per the Sarcopenia Definitions and Outcomes Consortium (SDOC) definition was significantly associated with grade ≥3 toxicity (adjusted odds ratio (OR): 2.77, 95%CI: 1.03–7.45, p = 0.044). SMI either as a continuous (OR: 1.03, 95%CI: 0.97–1.09, p = 0.40) or categorical variable (OR: 1.17, 95%CI: 0.47–2.89, p = 0.74) was not predictive of grade ≥3 toxicity. Similarly, low physical performance did not have significant associations with grade ≥3 toxicity (OR: 2.06, 95%CI: 0.86–4.95, p = 0.11). Conclusion Low grip strength may predict grade ≥3 toxicity among older adults receiving chemotherapy. Integrating grip strength into geriatric assessment may help clinicians identify older adults who might be at greater risk for severe chemotherapy toxicity.